Environmental, social, and governance perspectives on economic development in Asia - Barnett, William A.; Sergi, Bruno S. (Bingley, U.K. : Emerald Publishing Limited, 2021)
This volume of the International Symposia in Economic Theory and Econometrics explores the latest economic and financial developments in Asia. Chapters cover a range of topics such as the consequences of green supply chain integration and environmental uncertainty on performance, along with the effects of perceived organisational support, transformational leadership, and teamwork on employee engagement. These peer-reviewed papers touch on a variety of timely, interdisciplinary subjects such as corporate social responsibility and the effects of public policy. Environmental, Social, and Governance Perspectives on Economic Development in Asia also includes empirical studies in financial economics and public governance. For example, one chapter analyses the impact of COVID-19 pandemic risk and lockdown on the Indian economy, while another empirically studies the influence of word of mouth variables on visits and re-visits for ecotourism in West Java. Together, ISETE 29 volume B, is a crucial resource of current, cutting-edge research for any scholar of international finance and economics.
Chapter 1. The economic performance of China in trade war: The case study of three global economic crisis in 1997 - 2020 / Budi Sasongko, Suryaning Bawono, and Bambang Hadi Prabowo -- Chapter 2. Identifying neighborhood reinforcement method to enhancing socio-economic development in indonesia: A quintuple helix perspective / Vidya Purnamasari, Ermita Yusida, Vika Annisa Qurrata, Santi Merlinda, Linda Seprillina, and Wen-Chi Huang -- Chapter 3. Materiality analysis and CSR in micro, small, and medium enterprises / Erwin Saraswati -- Chapter 4. Green supply chain integration and environmental uncertainty to performance: The mediating role of green innovation / Siti Aisjah and Sri Palupi Prabandari -- Chapter 5. Entrepreneurial perspective on firm's environmental activities / Duangporn Puttawong and Anusorn Kunanusorn -- Chapter 6. Facing international environmental challenges by enhancing employee engagement / Reny Diana and B. Medina Nilasari -- Chapter 7. Innovation orientation, marketing capability, dynamic capability, and performance / Bahrun Borahima, Noermijati Noermijati, Djumilah Hadiwidjojo, and Ainur Rofiq -- Chapter 8. The interactive effect of ethical leadership and employee citizenship behaviour on organisational success: Do lenses of corporate governance matter? / Amy Yeo Chu May, Carmen Teoh Chia Wen, and Jeffton Low Boon Tiong -- Chapter 9. Entrepreneurship in the tourism industry: Implication on sustainable economic development / Murniati, Ghozali Maski, Iswan Noor, and Marlina Ekawaty -- Chapter 10. Investigation of taxation knowledge, services, and sanctions of the head of village government financial affairs of gunung kidul regency in Indonesia / Sang Ayu Putu Piastini Gunaasih -- Chapter 11. Impact of covid-19 pandemic risk and lockdown on the Indian economy / Soumya Bhadury -- Chapter 12. The impacts of electronic word of mouth on the intention of patients to join "in vitro fertilization" program / Muhammad Rizal, Endang Ruswanti, and Moehamma
Includes index.
Print version record.
Keywords: elektronické knihy; electronic books; Economic development -- Asia; Business & Economics -- Development -- Economic Development; Development economics & emerging economies; Asia -- Economic conditions -- 21st century